Effects of sacubitril/valsartan on the functional capacity of real-world patients in Italy: the REAL.IT study on heart failure with reduced ejection fraction - Sarullo, Filippo Maria; Nugara, Cinzia; Sarullo, Silvia; Iacoviello, Massimo; Di Gesaro, Gabriele; Miani, Daniela; Driussi, Mauro; Correale, Michele; Bilato, Claudio; Passantino, Andrea; Carluccio, Erberto; Villani, Alessandra; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Heart failure (HF) significantly affects the morbidity, mortality, and quality of life of patients. New therapeutic strategies aim to improve the functional capacity and quality of life of patients while controlling HF-related risks. Real-world data on both the functional and cardiopulmonary exercise capacities of patients with HF with reduced ejection fraction upon sacubitril/valsartan use are lacking. Methods A multicenter, retrospective, cohort study, called REAL.IT, was performed based on the data collected from the electronic medical records of nine specialized HF centers in Italy. Cardiopulmonary exercise testing was performed at baseline and after 12 months of sacubitril/valsartan therapy, monitoring carbon dioxide production (VCO2) and oxygen consumption (VO2). Results The functional capacities of 170 patients were evaluated. The most common comorbidities were hypertension and diabetes (i.e., 53.5 and 32.4%, respectively). At follow-up, both the VO2 peak (from 15.1 ± 3.7 ml/kg/min at baseline to 17.6 ± 4.7 ml/kg/min at follow-up, p < 0.0001) and the predicted % VO2 peak (from 55.5 ± 14.1 to 65.5 ± 16.9, p < 0.0001) significantly increased from baseline. The VO2 at the anaerobic threshold (AT-VO2) increased from 11.5 ± 2.6 to 12.5 ± 3.3 ml/kg/min (p = 0.021), and the rate ratio between the oxygen uptake and the change in work (ΔVO2/Δwork slope) improved from 9.1 ± 1.5 to 9.9 ± 1.6 ml/min/W (p < 0.0001). Conclusions Sacubitril/valsartan improves the cardiopulmonary capacity of patients with HFrEF in daily clinical practice in Italy.